Influence of test duration on oxygen uptake attained during treadmill running - James, D. V. B.; Sandals, L. E.; Draper, S. D.; Maldonado-Martin, S.; Wood, D. M. (European Journal of Sport Science, 2008)
Previous investigations have revealed that in well-trained middle-distance runners, oxygen uptake (VO2) does not attain maximal values (VO2max) in exhaustive treadmill trials where the VO2 demand exceeds VO2max. To date, this shortfall in the VO2 attained has been demonstrated in trials as short as 2 min in duration. In this study, we investigated whether a reduction in exhaustive test duration influences the VO2 attained during running on a treadmill. Six middle-distance runners participated in the study, completing an exhaustive 400 m and 800 m trial. These trials, together with a progressive test to determine VO2max, were completed in a counterbalanced order. Oxygen uptakes attained during the 400 m and 800 m trials were compared to examine the influence of exhaustive test duration. A plateau in VO2 was observed in all participants for the progressive test, demonstrating the attainment of VO2max. The mean speed, duration, and resulting distance in the constant-speed exhaustive trials were 25.8 km · h-1 (s=1.2), 55.8 s (s=2.3), and 400.2 m (s=20.2) for the 400 m trial, and 24.3 km · h-1 (s=0.8), 108.4 s (s=21.2), and 730.1 m (s=129.1) for the 800 m trial, respectively. A paired-samples t-test revealed a significantly different (P=0.018)%VO2max was attained for the 400 m (85.7%, s=3.0) and 800 m (89.1%, s=5.0) trials. In conclusion, VO2 did not reach VO2max during the exhaustive constant-speed 400 m and 800 m trials, but the test duration does influence the%VO2max achieved. Specifically, the VO2 attained becomes progressively further below VO2max as trial duration is reduced, such that 89% and 86% VO2max is achieved in exhaustive 800 m and 400 m constant-speed trials, respectively.